Using Blockchain Technology at Supply Chain: The Sample of Migros - Menekşe Cömert; Esra Kanoğlu; Hakan Güleç; Münevver Kaya (Turkish Journal of Agriculture: Food Science and Technology)
This study aims to determine the functionality and benefits of blockchain technology in food procurement. Within the scope of the study, Migros Trade Inc., a retail food supply company implementing blockchain technology in Türkiye, was examined as a case study. The study employed a qualitative research case study design, asking expert participants from Istanbul and Izmir to give their opinions on pre-designed themes, and conducting descriptive analyses of the data collected. The themes of the research are food supply chain, good agricultural practices, sustainability in food, blockchain applications in food supply and food safety. At the end of the study, it was found that the transparency and traceability principles of blockchain have a positive impact on consumers and supply chain stakeholders. However, challenges such as technical infrastructure and performance, as well as the reasons for not starting the process directly from the field, were the problems experienced. The data shows that blockchain technology is an efficient system that should be expanded in the food supply chain.